Assessing the barangay based mangrove protection and rehabilitation Barangay Nabitasan, Leganes, Iloilo - Yap, Mary Bel D.
Mangrove protection and rehabilitation/reforestation was essential to the government and non-government sectors, for the past years up to the present because of its ecological and economic benefits. This can also contribute to the slowing and reversing of negative impacts of the uncontrolled use of our coastal resources, which are known to be incredibly important to our country's security (Guidebook Series No. 2 of Philippines Coastal management 2001). Mangrove forest can support the natural production of Barangay Nabitasan, Leganes. The barangay found itself losing from the natural fishery production as a result of abandoned mangroves in the coastal areas. A law passed, Proclamation No. 2152 in 1981 - "Do not cut mangroves", this is a law which prohibits the cutting of mangroves. another mangrove law, the Department of Agriculture Order (DAO No. 10 1998) at present allows only Community-Based Forest Management Agreement (CBFMA) holders to harvest and prohibits the uprooting of trees and natural regeneration growing in the mangrove areas except collection of wildings for plantation purposes. The study were treated with the use of descriptive-analytical approach. It is aimed to: a) identify the present programs and activities of the local government in order to protect and rehabilitate/reforest the mangrove areas; b) identify the existing, mechanisms and strategies adopted by the barangay residents in terms of mangrove protection, rehabilitation/reforestation; c) specify the problems related to mangrove planting, protecting, and rehabilitating in their coastal areas; d) formulate and implement policies, ordinances/resolutions related to coastal management; e) provide conclusions and recommendations to protect, rehabilitate and reforest the mangrove areas. Most problems and issues related to mangrove protection, rehabilitation and reforestation are inter-linked and must be properly addressed to LGU planners, NGOs administrators, and policy makers. A holistic approach or strategy is necessary, considering the interfacing nature of problems at hand. Concerted efforts must be exerted by all sectors/agencies of the LGUs and the concerned people themselves to attain an effective CRMP for the betterment of the social and economic life of the fisherfolks and coastal residents of the barangay. With the conduct of bio-adversity conservation program of mangrove reforestation, and monitoring information on the ecosystem and bio-resources as well as oceanographic profile and water quality, planning and implementation of CRM program within the coastal areas of Barangay Nabitasan, will facilitate and provide the basic needs of the barangay population. The implementation of bio-diversity conservation program will increase the harvest of fish species, crabs and shrimps, because it will provide a good habitat and a breeding place for marine life. Another foreseeable impact is increased fish catch with the implementation of CRM. Sustainable management and protection of mangroves results in more and longer term benefits for a greater number of people and can continue to supply fish products, crustaceans, seashells, woods and other useful products with the minimum capital and labor. In contrast, intensive aquaculture is susceptible to disease, soil acidity problems, the vagaries of the market, and water quality problems, all of which undermine economic viability. This is why many shrimp farms have closed in the Philippines and elsewhere in Southeast Asia. This situation has resulted in many abandoned fishponds and degraded mangrove areas. In addition, existing environmental laws are to be implemented particularly the provisions under the DENR, and the Protected Areas Management Bureau (PAMB).